2020
DOI: 10.1590/0074-02760200313
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal multiple insecticide resistance in Aedes aegypti populations in French Guiana: need for alternative vector control

Abstract: BACKGROUND Aedes aegypti is the sole vector of urban arboviruses in French Guiana. Overtime, the species has been responsible for the transmission of viruses during yellow fever, dengue, chikungunya and Zika outbreaks. Decades of vector control have produced resistant populations to deltamethrin, the sole molecule available to control adult mosquitoes in this French Territory.OBJECTIVES Our surveillance aimed to provide public health authorities with data on insecticide resistance in Ae. aegypti populations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…These new results corroborated the previous efficacy measured against the susceptible Paea strain and the preliminary data obtained about the wild strain Cayenne (Falkowski et al 2016(Falkowski et al , 2020. The overall results are in accordance to resistance pattern towards pyrethroids described in French Guiana (Dusfour et al 2015;Faucon et al 2017;Guidez et al 2020;Senthil-Nathan 2020;Epelboin et al 2021). Besides lethality, the impact of active products on oviposition deterrence and repellence, as well as development, longevity or vitality of the target insect are also of great importance in the field of vector control (Borges et al 2019;Turchen et al 2020;Pavela et al 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These new results corroborated the previous efficacy measured against the susceptible Paea strain and the preliminary data obtained about the wild strain Cayenne (Falkowski et al 2016(Falkowski et al , 2020. The overall results are in accordance to resistance pattern towards pyrethroids described in French Guiana (Dusfour et al 2015;Faucon et al 2017;Guidez et al 2020;Senthil-Nathan 2020;Epelboin et al 2021). Besides lethality, the impact of active products on oviposition deterrence and repellence, as well as development, longevity or vitality of the target insect are also of great importance in the field of vector control (Borges et al 2019;Turchen et al 2020;Pavela et al 2021).…”
Section: Discussionsupporting
confidence: 86%
“…Nowadays, this French overseas territory faces a strong resistance of Ae. aegypti populations towards pyrethroids as adult vector-control products (Dusfour et al 2015;Faucon et al 2017;Guidez et al 2020;Senthil-Nathan 2020;Epelboin et al 2021). Bti (Bacillus thuringiensis var.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the massive usage of deltamethrin for years in FG 1,15 and the high frequencies of resistance alleles observed in FG. [4][5][6]15,20,21 Molecular data obtained from each line at the beginning of the experiment (G1) confirmed that most resistance markers monitored in this study were at a higher frequency in the FG line than in the NC line. In the FG line all individuals harbored at least two kdr mutations and seven detoxification genes out of nine tested were overtranscribed as compared to the susceptible strain.…”
Section: Discussionsupporting
confidence: 77%
“…This information is important to adapt vector control strategies in both countries. Today, the level of resistance in French Guiana is critical with the fixation of target-site mutations and co-occurrence with metabolic mechanisms (Dusfour et al, 2015;Guidez et al, 2020). Other paths are also being investigated to determine the implication of the microbiome in the detoxification of insecticides.…”
Section: Resistance In the Amazonian Context: Specific Adaptive Responses Of Parasites And Vectors Under High Selective Pressurementioning
confidence: 99%
“…darlingi, such as Culex quinquefasciatus. This particular Culicid species is known to adapt quickly to insecticide pressure (Guidez et al, 2020). A novel vector in the environment would deeply challenge the wellestablished vector control strategies as developed in French Guiana during the last few decades.…”
Section: Resistance In the Amazonian Context: Specific Adaptive Responses Of Parasites And Vectors Under High Selective Pressurementioning
confidence: 99%